Efficient use of land areas created by lowering the level of the Caspian sea - Shirinova, D B; Cavadova, Ch A; Huseynova, M A; Bagirova, N N; Abdullayeva, K S (IOP conference series. Earth and environmental science, 2023)
The reasons for the change in the level of the Caspian Sea, predictions of the level change, comparisons, analysis of soil samples taken from the coastal area 35 m away from the sea for use in the analysis of the lands caused by the lowering of the sea level were carried out. Separated areas were washed with mixed proportions of domestic sewage, seawater + domestic sewage and seawater + domestic sewage + ordinary (fresh) water. After washing in those areas, the salt content of the soil was studied. Plants of the same name were planted in both areas and watered with the mentioned washing waters. It has been found that the area irrigated with a mixture of household sewage water + normal water (1:1) can be more productive.